Avaliação dos efeitos da indução da resposta inflamatória aguda em modelos experimentais bovinos desafiados com LPS endovenoso e vacinação - Silva, Beatryz Fonseca da (2024)
The aim was to evaluate the effects of inducing the acute inflammatory response in different bovine categories of crossbred cattle (Gir x Holstein) raised in a tropical climate Two studies were conducted: a) study 1, the objective was to evaluate the effects of the local and systemic acute inflammatory response through a single vaccination dose, using an inactivated multivalent commercial vaccine; b) study 2, with the objective of evaluating the effects of experimentally induced endotoxemia with LPS intravenous administration derived from Escherichia coli in crossbred dairy calves. In study 1, 68 lactating cows were used, 31 primiparous and 37 multiparous. The animals were evaluated by measuring rectal temperature, vaccination site, white blood cell count, total proteins and fractions, acute phase protein and milk yield on the days before (D-7 and D0) and after vaccination (D+1, D+3 and D+7). There was an increase in rectal temperature (D+1) in both primiparous (P=0.0013) and multiparous (P=0.0002) cows. At D+7, all animals had a local reaction (P<0.0001). Systemic reaction was observed in multiparous cows concerning leukocytosis and neutrophils at D+1. The multiparous cows showed an increase in the serum haptoglobin concentration (D+3 and D+7), and fibrinogen (D+3). While there was a change in fibrinogen (P=0.0101) in primiparous cows at D+3. Both categories showed reductions in milk yield at D+1, with a decrease of 10% for primiparous and 9.2% for multiparous. In study 2, 11 crossbred calves aged three to eight months were used and divided into two experimental groups: control group (n.4), and challenge-LPS group (n.7). The animals received an intravenous boluses of saline solution or LPS derived from E. coli (0111:B4), at a dose of 0.5 μg of LPS/kg body weight. The general clinical examination, electrocardiogram, indirect blood pressure measurement, complete blood count, glycemia, venous lactate and cytokines were carried out. The goup challenged with LPS presented tachypnea at T +1h (P= 0.026), with an increase of 57.6% to the pre-challenge value, and tachycardia at T +3h (P= 0.020) with an increase of 31.9%. The LPS infusion reduced glucose concentration 8 h after challenge and increased venous lactate concentrations. In addition, the challenge significantly increased plasma concentrations of interleukin IL1β with peaks at 1.5 h and IL 6 at 3 h after LPS challenge. One hour after LPS administration, 75% of calves showed conduction disturbances caused by 2- degree atrioventricular block, and six hours after LPS one animal showed ventricular tachyarrhythmia. The results of these studies suggest that vaccination in cows (study 1) and administration of LPS derived from E. coli in crossbred calves raised in a tropical climate (study 2) induced clinical and inflammatory changes of a short-duration acute-phase response, safe and reproducible.